Disassembling technologies of precise friction pair - Кудрін, А.П. (Problems of Tribology, 2015)
Kudrin A.P. Disassembling technologies of precise friction pair. Purpose of the work is to analyze the conception of disassembling technologies of precise friction pair detail’s restoration. The management principles of tribosystem of development of realization of triboelectrochemical and tribomagnetic processes of reparation on the basis of tribosystem model upon condition of friction and sliding and action of external electric and magnetic fields. Tribosystem controlling in the direction of development of reparation development can be performed either by use of energy parameters of electric and magnetic fields or by means of friction materials using.of electrod-supply materials, working conditions and friction regime.